2019
DOI: 10.7287/peerj.preprints.27531
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuropeptides in modulation of Drosophila behavior: how to get a grip on their pleiotropic actions

Abstract: Neuropeptides constitute a large and diverse class of signaling molecules that are produced by many types of neurons, neurosecretory cells, endocrines and other cells. Many neuropeptides display pleiotropic actions either as neuromodulators, co-transmitters or circulating hormones, while some play these roles concurrently. Here, we highlight pleiotropic functions of neuropeptides and different levels of neuropeptide signaling in the brain, from context-dependent orchestrating signaling by higher order neurons,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Neuropeptides constitutes a large and diverse class of signaling molecules that are produced by various types of neurons, which modulates many insect behaviours and physiology [3,4]. Recent advances in neurobiological research have suggested that neural circuits encompassing neuropeptide relay signaling are essential modulators for various behaviours, including feeding, energy homeostasis, sleep and wakefulness [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Neuropeptides constitutes a large and diverse class of signaling molecules that are produced by various types of neurons, which modulates many insect behaviours and physiology [3,4]. Recent advances in neurobiological research have suggested that neural circuits encompassing neuropeptide relay signaling are essential modulators for various behaviours, including feeding, energy homeostasis, sleep and wakefulness [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of ArSK/CCK1 and ArSK/CCK2 in triggering cardiac stomach retraction in A. rubens (see above) suggested that SK/CCK-type signalling may have a physiological role in inhibition and/or termination of feeding behaviour in starfish, which would be consistent with the physiological roles of SK/CCK-type neuropeptides in other taxa ( Al-Alkawi et al, 2017 ; Downer et al, 2007 ; Kang et al, 2011 ; Maestro et al, 2001 ; Meyering-Vos and Müller, 2007 ; Nachman et al, 1986b ; Nässel et al, 2019 ; Rehfeld, 2017 ; Roman et al, 2017 ; Wei, 2000 ; Yu et al, 2013a ; Zels et al, 2015 ; Zhang et al, 2017 ). Therefore, we performed experiments to specifically investigate if ArSK/CCK1 and ArSK/CCK2 have inhibitory effects on starfish feeding behaviour on prey (mussels).…”
Section: Resultsmentioning
confidence: 56%
“… Sensory systems are dynamically adjusted according to the animal’s ongoing needs by neuromodulators, such as neuropeptides. Despite their prevalence across all nervous systems 1,2 , how peptidergic neurons and the neuropeptide they release act to adjust sensory processing remains poorly understood. Here, we reveal that a heterogeneous ensemble of local interneurons (LNs) release the neuropeptide myoinhibitory peptide (MIP) within the Drosophila primary olfactory center (the antennal lobe, AL).…”
mentioning
confidence: 99%